Ladder shaped RF mems switch for wireless application - Saud Khan, Aamir; Shanmuganantham, T (International Journal of Engineering and Technology, 2018)
This paper analyses the different position of actuation electrode in an inline ladder shaped cantilever beam Radio Frequency (RF) Microelec-tromechanical System (MEMS) switch, which shows very good RF parameters over the range of (0-50) GHz along with low actuation voltage. The switch is designed and simulated by software Intellisuite 8.7v for electromechanical analysis and by EM software for RF anal-ysis. From the simulated results, they obtained a low actuation voltage (2 V). It shows a very less insertion loss -0.008 dB at 8 GHz and high isolation loss â€“100 dB at 8 GHz.Â